Five Ways to Create an Oil Mosaic - Artist Salome Chelidze (Peerian Journals Publishing, 2022)
Oil mosaic is my author's invention as an actual and new style in contemporary art. It turned out to be a very interesting art, which was responded to by many world-famous galleries, people who were interested in the technique and method of converting a canvas into an imitation of a stained-glass window. They also often wonder how to paint oil murals in layers that do not look like oil paint, and the viewer visually thinks that it is a stone or a precious metal, in many cases they think the same thing about textiles, because the secret of oil mosaic is multilayer compositions., which are works of art of great interest to people.
Keywords: oil mosaic; color palette; paintings; contemporary art